The The Effect Of Regional Original Income, Regional Financial Management And Accountability On Development Performance Of Mamuju District - Zulcarnaim Zulcarnaim (Cita konsultindo, 2023)
One very crucial aspect of decentralization (regional autonomy) is the issue of fiscal decentralization. Conceptually, fiscal decentralization requires that each authority given to the regions must be accompanied by financing that is in accordance with the burden of that authority. In other words , the central government is obliged to guarantee financial resources for the delegation of tasks and authority from the center to the regions. Responding to these problems, the government issued Law Number 33 of 2004 concerning Financial Balance between the Central Government and Regional Governments. Based on the Mamuju District Government Realization Report for 2016-2019, that local revenue has increased every year from 2016 to 2019, but for balancing funds there have been fluctuations where in 2016-2017 it has decreased and from 2018-2019 there has also been a decrease in the amount of funds. Good regional financial management will affect the progress of a region. Regional financial management that is carried out economically, efficiently and effectively or fulfills the principles of value for money as well as participation, transparency, accountability and justice will be able to encourage economic growth. Good regional financial management not only requires reliable human resources but also must be supported by adequate regional financial capacity. The ability level of a region can be measured by the amount of regional revenue.